(3GdTQcGJ GdJLGQjI (B:s (3GdfXQjI GdYGeI ddTQcGJ(B-(3TQcI GdJVGef(B- (3TQcI GdJhUjI GdHSjWI (B/s - (3GdYQjfj, eMeO aQjOs ((3GdGScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2002)
(3aj GdTQcI cYbO(B- (3aj GdTQcI cTNU eYfhj(B- (3aj Md GdTQcI hEfbVGFgG(B- (3aj JUajI GdTQcGJ hbSeJgG(B-(3aj TQcGJ GdCTNGU , aj TQcGJ GdJVGef (B-(3aj TQcI GdJhUjI GdHSjWI(B- (3aj TQcGJ GdeSGgeI(B- (3aj TQcI GdCehGd(B- (3TQcI GdJhUjI HGdCSge(B- (3TQcGJ PGJ GdeSDhdjI GdeMOhOIs
Keywords: (3GdJLGQIs; (3GdTQcGJs; (3GdYbhOs